Establishment of lower exhaust emissions by using EGR coupled low heat loss diesel engine with fuel blends of microalgae biodiesel-oxygenated additive DEE-antioxidant DPPD. (October 2019) - Krishna Kolli, Vamsi; Gadepalli, Sastry; Deb Barma, John; Krishna Maddali, Murali; Barathula, Sreeram; Kumar reddy Siddavatam, Naresh
Highlights: The YSZ ceramic coated engine is well suited for microalgae biodiesel-additive blends. Additive DEE improved cetane number, oxygen content and viscosity of the biodiesel. The antioxidant additive DPPD with biodiesel substantially reduced the NOx emissions. An economic contribution for engine emissions-performance improvement had carried out. Abstract: The aims of the research work are: Achieving maximum reduction in the exhaust emissions of the diesel engine and investigate the potentiality of a higher ratio of biodiesel blended with suitable additives as an alternative for diesel fuel. Herein, a coated engine (CE) was produced by the application of bond coating NiCrAlY on the cylinder head and liner substrate, further it was coated with 8 mol.% Yttria-stabilized zirconia (8-YSZ) ceramic. The YSZ restrict the in-cylinder combustion heat loss to the coolant and combustion chamber components due to its low thermal conductivity. The CE was coupled with an exhaust gas recirculation (EGR) system at an optimal constant rate of 10% by vol. to reduce the formation of NOx emissions. Fuel blends with different combinations of microalgae (Chlorella protothecoides) oil-based biodiesel (MB) and additives diethyl ether (DEE), amine antioxidant N, N′-diphenyl-1, 4-phenylenediamine (DPPD) were synthesized and tested. The experiment was carried out by scrutinizing the emissions and performance of CE fuelled by blends with a comparison to the uncoated engine (UE) with diesel at different load conditions. The results had shown that the additives enhanced the oxidation stability, cetane number while decreasing the viscosity of the biodiesel. The EGR coupled CE displayed improvement in all the investigated parameters with optimum of particulate emissions by 45.5%, un-burnt hydrocarbons by 51%, NOx by 18.5, CO emissions by 47%, peak brake thermal efficiency by about 6% and brake specific fuel consumption by 8.5% found for the blend MB85DEE15DPPD 1000 ppm (microalgae biodiesel 85%+ diethyl ether 15%+DPPD 1000 ppm) at 80% load. This work made a substantial approach to an economic contribution by simultaneously addressing global issues like air-pollution and fossil fuel crisis.